Pemberdayaan Lansia Melalui Implementasi Model Desain Partisipatoris di Sekolah Lansia Gedongkiwo, Yogyakarta - Calya Ayu Putri Salsabilla; Danang Febriyantoko; Dewi Cahyani Puspitasari (Direktorat Pengabdian kepada Masyarakat, 2026)
Indonesia's rapidly growing older population calls for empowerment models that transform perceptions of seniors from passive recipients into active, resilient community members. This publication explores the Gedongkiwo Elderly School as an empowerment example within the Age-Friendly Communities framework, combining community learning and participatory design. The community engagement took place in Gedongkiwo Village, Yogyakarta City, the province with Indonesia's highest percentage of older adults. The program used a community learning approach to identify local needs and promote reflective learning among older adults, community cadres, and local officials. The program aims to create a participatory design that addresses the needs of the elderly in the Gedongkiwo area. The results of this design will be used by stakeholders such as the Gedongkiwo Village Administration, the Integrated Elderly Services (LLT) management, posyandu cadres, and the elderly themselves. It then employed observation, interviews, and focus groups to develop recommendations for age-friendly spatial designs. Results show that participatory methods boost social involvement, foster older adults' sense of ownership, and lead to better design suggestions for public facilities that are safer, more inclusive, and adaptable. Key outcomes include designing green public spaces and elderly learning centers that enhance mobility, social interaction, and comfort for seniors. Socially, the initiative helped older individuals become more confident, connected, and empowered contributors to community development. The study concludes that combining community learning with participatory design is an effective strategy for elderly empowerment within the Age-Friendly Community framework, offering a promising model for replicating age-friendly public infrastructure at the local level